A statistical study towards high-mass BGPS clumps with the MALT90 survey. (January 2018) - Liu, Xiao-Lan; Xu, Jin-Long; Ning, Chang-Chun; Zhang, Chuan-Peng; Liu, Xiao-Tao
Abstract: In this work, we perform a statistical investigation towards 50 high-mass clumps using data from the Bolocam Galactic Plane Survey (BGPS) and Millimetre Astronomy Legacy Team 90-GHz survey (MALT90). Eleven dense molecular lines (N2 H + (1–0), HNC(1–0), HCO + (1–0), HCN(1–0), HN 13 C(1–0), H 13 CO + (1–0), C2 H(1–0), HC3 N(10–9), SiO(2–1), 13 CS(2–1)and HNCO(44, 0 − 30, 3 )) are detected. N2 H + and HNC are shown to be good tracers for clumps in various evolutionary stages since they are detected in all the fields. The detection rates of N-bearing molecules decrease as the clumps evolve, but those of O-bearing species increase with evolution. Furthermore, the abundance ratios [N2 H + ]/[HCO + ] and log([HC3 N]/[HCO + ]) decline with log([HCO + ]) as two linear functions, respectively. This suggests that N2 H + and HC3 N transform to HCO + as the clumps evolve. We also find that C2 H is the most abundant molecule with an order of magnitude 10 −8 . In addition, three new infall candidates, G010.214–00.324, G011.121–00.128 and G012.215–00.118(a), are discovered to have large-scale infall motions and infall rates with an order of magnitude 10 −3 M ⊙ yr −1 .